2019
DOI: 10.1111/jav.01877
|View full text |Cite
|
Sign up to set email alerts
|

Non‐breeding areas and timing of migration in relation to weather of Scottish‐breeding common sandpipers Actitis hypoleucos

Abstract: The number of breeding common sandpipers has declined in Britain due to poorer return rates from non‐breeding areas. To investigate little known aspects of their annual cycle, breeding common sandpipers were fitted with geolocators to track their migrations and determine their non‐breeding areas. Ten tagged birds left Scotland on 9 July (median dates and durations are given throughout the abstract). Short‐term staging was carried out by some birds in England and Ireland, then for longer by most birds in Iberia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 29 publications
3
26
2
Order By: Relevance
“…Low impact of weather effects Surprisingly, our ndings provided no evidence for weather as a migration trigger in curlews, in contrast to various other bird species [12,24,[31][32]. However, our data con rmed that ight speed increased with increasing TWC, in accordance with previous studies [6,29].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Low impact of weather effects Surprisingly, our ndings provided no evidence for weather as a migration trigger in curlews, in contrast to various other bird species [12,24,[31][32]. However, our data con rmed that ight speed increased with increasing TWC, in accordance with previous studies [6,29].…”
Section: Discussionsupporting
confidence: 86%
“…We proposed ve hypotheses. (1) Given that tailwinds will increase ight and migration speeds [6; 29-30], we expected curlews to time their departure from and arrival at their wintering grounds according to favourable wind and weather conditions, especially in relation to tailwind conditions, lack of precipitation, and air temperature, as found in other bird species [12,24,[31][32]. (2) In line with this, we expected ight heights (as recorded by GPS tags) to increase during non-tailwind conditions to allow the birds to reach air layers with improved wind conditions [22,33].…”
Section: Introductionmentioning
confidence: 99%
“…(2) Individuals of a range of bird species have been shown to time their departure according to favourable wind and weather conditions (e.g. a tailwind and no or little precipitation; [12,[22][23][24]. In line with our rst hypothesis, we therefore expected curlews to time their departure from and arrival at their wintering grounds according to favourable wind and weather conditions, especially in relation to tailwind conditions and lack of precipitation.…”
Section: Introductionmentioning
confidence: 62%
“…However, in contrast to our assumption, the current study revealed virtually no effect of wind or other weather parameters on the departure/arrival day for curlews, even when the actual weather during departure was compared with the mean weather conditions 4 days and/or 4 years prior to departure. Although curlews rarely departed during hours with precipitation (in accordance with other bird species) [12,[23][24], this predictor had no signi cant in uence in our nal model. The current ndings were therefore not in agreement with previous studies, which found that the probability of departure of curlews from a pre-breeding staging site was reduced during precipitation [46].…”
Section: Discussionmentioning
confidence: 80%
“…These individuals were carrying thinner and lighter tags than those tagged in the UK. The only other study to attach geolocators to Common Sandpipers using leg flags did not report any adverse effects, but used tags similar in size and weight to those we deployed in Senegal (Summers et al 2019). Given the prevalence of tracking studies carried out on many different species, it is surprising that no others that we know of have reported tags causing limb loss.…”
Section: Discussionmentioning
confidence: 97%